2022
DOI: 10.3389/fnut.2022.919651
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms in gene MTHFR modify the association between gestational weight gain and adverse birth outcomes

Abstract: Evidence suggests a potential relationship between gestational weight gain (GWG) and adverse birth outcomes. However, the role of maternal genetic polymorphisms remains unclear. This study was conducted to investigate whether the relationship of GWG with risk of adverse birth outcomes was modified by methylenetetrahydrofolate reductase (MTHFR) polymorphisms. A total of 2,967 Chinese pregnant women were included and divided into insufficient, sufficient, and excessive groups based on the Institute of Medicine (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 44 publications
0
9
0
Order By: Relevance
“…An MTHFR polymorphism leads to enzyme dysfunction, possibly resulting in higher Hcy levels and disturbances in one-carbon metabolism. Thus, MTHFR gene variants have been linked to many metabolic pathologies, including gestational weight gain [ 1 ]. The MTHFR gene has 12 exons and is located on chromosome 1 (1p36.22).…”
Section: Introductionmentioning
confidence: 99%
“…An MTHFR polymorphism leads to enzyme dysfunction, possibly resulting in higher Hcy levels and disturbances in one-carbon metabolism. Thus, MTHFR gene variants have been linked to many metabolic pathologies, including gestational weight gain [ 1 ]. The MTHFR gene has 12 exons and is located on chromosome 1 (1p36.22).…”
Section: Introductionmentioning
confidence: 99%
“…30 The interaction between C677T polymorphisms and obesity in patients with type 2 diabetes was also 0.05-0.76). 14 Similarly, our previous studies had indicated that pregnant women who were obese, with the CT þ TT genotype, were 2.40 times more likely to have GDM, whereas no significant association was observed in those with the CC genotype. 31 In addition, an…”
Section: Discussionmentioning
confidence: 73%
“…Heterozygous, homozygous, dominant, recessive, and additive models were used to explore the associations between genetic polymorphisms and adverse birth outcomes. To analyse the potential interaction effects of genetic variants on the association between HbA1c levels and adverse birth outcomes, the participants were divided into non‐mutated and mutated groups for better statistical power, similar to previous studies 14,15 . The likelihood ratio test was used to calculate the p ‐value for multiplicative interactions, among which the differences in the likelihood scores of the two models with and without the interaction term of genotypes and HbA1c levels were compared.…”
Section: Methodsmentioning
confidence: 99%
“…There is increasing concern regarding whether genetic polymorphisms within lipid metabolism or nutritional factors in pregnant women are associated with the development of pregnancy outcomes [ 11 ]. Among them, methylenetetrahydrofolate reductase (MTHFR) plays an important role in the enzymatic process for maintaining folate metabolism and homocysteine methylation, which are considered risk factors during pregnancy [ 12 14 ]. The C677T and A1298C variants in MTHFR are two common single nucleotide polymorphisms (SNPs), and these variants have also been associated with several pregnancy complications, but the results were different.…”
Section: Introductionmentioning
confidence: 99%